USM ORGANISES TALK ON ESD BY PROFESSOR CHARLES HOPKINS AT DEWAN BUDAYA - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
The Regional Centre of Expertise on Education for Sustainable Development (RCE ESD) Penang@USM in (mailto:Penang@USM in) collaboration with Universiti Sains Malaysia (USM) School of Educational Studies will be organising a public lecture by Professor Charles Hopkins on Tuesday, 24 January 2017, at 9.15 a.m. at the Dewan Budaya, USM.